Risk Management in Islamic Banking - Abu Hardan, Yousef (2020)
Risk management is an integral part of banks’ activities and the banking industry is generally considered one of the riskiest types of businesses. Therefore, the present study aims to examine the risk management practices in Islamic banking, using Ajman bank as the case study. The methodology used in this study is qualitative based on structured interview. The analysis is based on face-to-face interviews with five heads of departments including Retail Banking Department, Internal Control Department, Sharia Department, Compliance and Risk Management (liquidity) Department. The results show that Ajman bank has effective risk management practices. The Risk Management department displays proper control for risk mitigation and the bank in accordance with the Sharia compliant. In addition, the findings reveal that the bank comply with Basel requirements and UAE Central Bank regulations.